The Effectiveness of Digital HR Management System on Work Efficiency through Digital Work Empowerment and Technology Acceptance at Lampung Post - Diah Anggraeni; Febrianty; Reza Hardian Pratama (International Journal of Management, Economic and Accounting, 2026)
Digital transformation in human resource management (HRM) has become a strategic necessity for modern organizations, including media industries such as Lampung Post. This study aims to examine the effectiveness of digital HR management systems on work efficiency through two mediating variables: digital work empowerment and technology acceptance. A quantitative survey approach was applied, involving Lampung Post employees who actively use the digital HRM system. Data were analyzed using path analysis to test both direct and indirect effects among variables. The findings reveal that the digital HRM system has a positive and significant effect on work efficiency. Furthermore, digital work empowerment and technology acceptance act as mediating variables that enhance the system’s impact on efficiency, demonstrating that empowered and technologically receptive employees are key to maximizing digital HR effectiveness. This study contributes to the development of digital HRM theory and provides practical insights for media organizations seeking to improve efficiency through digital empowerment and enhanced technology adoption. It also recommends strengthening employees’ digital capabilities to ensure sustainable implementation of HR digitalization in the future.